The effect of bed size and shading on straw mushroom productivity - Yadav, Awadh Narain; Peacock, Christabel P.; Gartner, Joseph A.; Tontyaporn S.; Deutscher Akdemischer Austanschdienst (DAAD) (German Academic Exchange Service) (Bangkok : Asian Institute of Technology, 1988)
Two experiments on the farmer's identified problems on straw mushroom (Volvariella volvacea) productivity were conducted at AIT. Experiment I was conducted with different bed sizes and the Experiment II with different degrees of shade. The temperature, relative humidity of both bed and the environment and the fresh yield of mushrooms were recorded. In the bed size experiment conducted in February/March, it was found that the bed height affected the bed temperature. The temperature increased with the bed height and affected the mushroom yield. The high bed size having the highest temperature yielded the lowest . The low and medium beds having a temperature range between 360c to 400c yielded the highest. These two beds yielded the similar in terms of per kilogram of substrate. The experiment with shade in April, showed that the straw mushroom yield under full shade was significantly higher than the partial and no shade treatments. It was also higher than that of the same bed size in February/March crop by 4. 3 %. Straw mushroom growing as a catch crop from February to April is a profitable enterprise. It returns to family labour three times as high as the opportunity cost of labour. With the available on - farm resources the potentiality exists for increasing the current farming scale of straw mushroom by upto 1. 8 times.
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Science, School of Environment, Resources and Development
Thesis (M.Sc.) - Asian Institute of Technology, 1988
Keywords: Mushroom culture